Trzy pojęcia sytuacji w filozofii nauki - Krajewski, Władysław (Filozofia Nauki, 1998)
The author analyses three concepts of situation in the philosophy of science: the problem situation (due to Karl Popper), the discovery-generating situation (due to Elżbieta Pietruska-Madej) and the solution-yielding situation (due to Jan Such). His thesis is, that the set of solution-yielding situations is a subset of the set of discovery-generating situations, which is contained in the set of problem situations.